Integrating palliative care across settings: A retrospective cohort study of a hospice home care programme for cancer patients. (July 2016) - Tan, Woan Shin; Lee, Angel; Yang, Sze Yee; Chan, Susan; Wu, Huei Yaw; Ng, Charis Wei Ling; Heng, Bee Hoon
Background: Terminally ill patients at the end-of-life do transit between care settings due to their complex care needs. Problems of care fragmentation could result in poor quality of care. Aim: We aimed to evaluate the impact of an integrated hospice home care programme on acute care service usage and on the share of home deaths. Settings/participants: The retrospective study cohort comprised patients who were diagnosed with cancer, had an expected prognosis of 1 year or less, and were referred to a home hospice. The intervention group comprised deceased patients enrolled in the integrated hospice home care programme between September 2012 and June 2014. The historical comparison group comprised deceased patients who were referred to other home hospices between January 2007 and January 2011. Results: There were 321 cases and 593 comparator subjects. Relative to the comparator group, the share of hospital deaths was significantly lower for programme participants (12.1% versus 42.7%). After adjusting for differences at baseline, the intervention group had statistically significantly lower emergency department visits at 30 days (incidence rate ratio: 0.38; 95% confidence interval: 0.31–0.47), 60 days (incidence rate ratio: 0.61; 95% confidence interval: 0.54–0.69) and 90 days (incidence rate ratio: 0.69; 95% confidence interval: 0.62–0.77) prior to death. Similar results held for the number of hospitalisations at 30 days (incidence rate ratio: 0.48; 95% confidence interval: 0.40–0.58), 60 days (incidence rate ratio: 0.71; 95% confidence interval: 0.62–0.82) and 90 days (incidence rate ratio: 0.77; 95% confidence interval: 0.68–0.88) prior to death. Conclusion: Our results demonstrated that by integrating services between acute care and home hospice care, a reduction in acute care service usage could occur.